2015
DOI: 10.1038/ncomms8629
|View full text |Cite
|
Sign up to set email alerts
|

Farnesoid X receptor inhibits glucagon-like peptide-1 production by enteroendocrine L cells

Abstract: Bile acids (BA) are signalling molecules which activate the transmembrane receptor TGR5 and the nuclear receptor FXR. BA sequestrants (BAS) complex BA in the intestinal lumen and decrease intestinal FXR activity. The BAS-BA complex also induces Glucagon-Like Peptide-1 (GLP-1) production by L-cells which potentiates β-cell glucose-induced insulin secretion. Whether FXR is expressed in L-cells and controls GLP-1 production is unknown. Here we show that FXR activation in L-cells decreases proglucagon expression b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
265
4
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 313 publications
(304 citation statements)
references
References 44 publications
16
265
4
1
Order By: Relevance
“…Furthermore, treatment with a gut-specific FXR agonist, fexaramine, reduces diet-induced increases in hepatic glucose production in mice, likely due to a robust increase in FGF 15 (Fang et al 2015). In contrast, some studies suggest that intestinal inhibition of FXR may in fact be beneficial via a reduction in intestinally derived ceramides , Jiang et al 2015, or via increased GLP-1 signalling (Trabelsi et al 2015), warranting further research into FXR agonism/antagonism for the treatment of diabetes. Interestingly, it has also been proposed that FXR-mediated metabolic improvements are due to alterations of the gut microbiota (Ryan et al 2014).…”
Section: Bile Acidsmentioning
confidence: 93%
“…Furthermore, treatment with a gut-specific FXR agonist, fexaramine, reduces diet-induced increases in hepatic glucose production in mice, likely due to a robust increase in FGF 15 (Fang et al 2015). In contrast, some studies suggest that intestinal inhibition of FXR may in fact be beneficial via a reduction in intestinally derived ceramides , Jiang et al 2015, or via increased GLP-1 signalling (Trabelsi et al 2015), warranting further research into FXR agonism/antagonism for the treatment of diabetes. Interestingly, it has also been proposed that FXR-mediated metabolic improvements are due to alterations of the gut microbiota (Ryan et al 2014).…”
Section: Bile Acidsmentioning
confidence: 93%
“…Another bile acid receptor is GPR TGR5, which increases thermogenesis and energy expenditure in BAT [60]. Both FXR and TGR5 are expressed on enteroendocrine L-cells and regulate GLP-1 synthesis: TGR5 induces GLP-1 synthesis [60], whereas FXR activation reduced it [61]. Thus, the intestinal microbiota may ultimately influence lipid uptake and host glucose metabolism through its effects on bile acids.…”
Section: Bile Acid Metabolismmentioning
confidence: 99%
“…Intestinal FXR knockout animals have been shown to be resistant to diet-induced obesity, insulin resistance, and NAFLD (58)(59)(60). It has also been shown that loss of intestinal FXR activity leads to induced GLP-1 (glucagon-like peptide 1) production, which leads to improved glucose metabolism (61). We saw a larger bile acid pool with a high hydrophobicity index in the SI of Arv1 -/ -animals.…”
Section: Arv1mentioning
confidence: 61%